The Maelstrom of Paris Based on a Novel by Germaine Acremant - Coppola, Antonio; Acremant, Germaine (Cinema of Discovery: Julien Duvivier in the 1920s, 2021)
A well-told story of a woman who thinks she prefers a life of glory on stage in Paris to life with her Scottish lord of a husband in his castle. [mubi.com]